Context dependency of rewards and services in an Indian ant–plant interaction: southern sites favour the mutualism between plants and ants. (22nd April 2014) - Chanam, Joyshree; Kasinathan, Srinivasan; Pramanik, Gautam K.; Jagdeesh, Amaraja; Joshi, Kanchan A.; Borges, Renee M.
Abstract: Protection-based ant–plant mutualisms may vary in strength due to differences in ant rewards, abundance of protective ants and herbivory pressure. We investigated geographical and temporal variation in host plant traits and herbivory pressure at five sites spanning the distribution range of the myrmecophyte Humboldtia brunonis (Fabaceae) in the Indian Western Ghats. Southern sites had, on average, 2.4 times greater abundance of domatia-bearing individuals, 1.6 times greater extrafloral nectary numbers per leaf, 1.2 times larger extrafloral nectary sizes, 2.2 times greater extrafloral nectar (EFN) volumes and a two-fold increase in total amino acid and total sugar concentrations in EFN compared with northern sites. A strong protection-based mutualism with ants occurred at only one southern site where herbivory was highest, suggesting that investments in attracting ants correlate with anti-herbivore benefits gained from the presence of protective ants. Our results confirm a temporally stable north–south gradient in myrmecophytic traits in this ant-plant as several of these traits were re-sampled after a 5-y interval. However, the chemical composition of EFN varied at both spatial and short-term temporal scales suggesting that only repeated measurements of rewards such as EFN can reveal the real spectrum of trait variation in an ant–plant mutualistic system.